The Relationship Between Self-Stigma Levels and Medication Compliance in Patients with Severe Mental Disorders - Dwi Lestari, Hernida; Pramujiwati, Desy; Sutisna, Didi; Suciana, Ewin (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2025)
Background: Medication adherence is a key factor in the successful treatment of patients with severe mental illness. However, the level of non-adherence remains relatively high and is often associated with various psychosocial factors, one of which is self-stigma. Self-stigma can influence patients' perceptions of the disease and treatment, potentially reducing adherence to regular medication use. Objective: This study aims to analyze the relationship between self-stigma levels and medication adherence in patients with severe mental illness. Methods: This study used a quantitative design with a cross-sectional approach. A total of 220 patients with severe mental illness undergoing treatment at a mental health service facility became the study respondents. The level of self-stigma was measured using the Internalized Stigma of Mental Illness (ISMI), while medication adherence was measured using the Medication Adherence Rating Scale (MARS). Data analysis was performed descriptively and inferentially using the Spearman correlation test and logistic regression with a significance level of p < 0.05. Results: The results showed that most respondents had moderate to high levels of self-stigma and more than half of respondents were non-compliant with medication. There was a significant negative relationship between self-stigma and medication adherence (r = −0.462; p < 0.001). Patients with high self-stigma are at greater risk of non-adherence to treatment. Conclusion: Self-stigma is significantly associated with medication adherence in patients with severe mental illness. Interventions focused on reducing self-stigma need to be integrated into mental health services to improve medication adherence and patient outcomes.